ALGORITHM FOR MANAGEMENT OF HYPERTENSIVE PATIENTS UNDERWENT UROLOGY INTERVENTIONS - S. S. Davydova (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study the efficacy of cardiovascular non-invasive complex assessment and pre-operative preparation in hypertensive patients needed in surgical treatment of urology dis- eases.Material and methods. Males (n=883), aged 40 to 80 years were included into the study. The main group consisted of patients that underwent laparotomic nephrectomy (LTN group; n=96) and patients who underwent laparoscopic nephrectomy (LSN group; n=53). Dynamics of ambulatory blood pressure monitoring (ABPM) data was analyzed in these groups in the immediate postoperative period. The efficacy of a package of non-invasive methods for cardiovascular system assessment was studied. ABPM was performed after nephrectomy (2-nd and 10-th days after surgery) in patients with complaints of vertigo episodes or intense general weakness to correct treatment.Results. In LTN group hypotension episodes or blood pressure (BP) elevations were observed in 20 (20.8%) and 22 (22.9%) patients, respectively, on the 2-nd day after the operation. These complications required antihypertensive treatment correction. Patients with hypotension episodes were significantly older than patients with BP elevation and had significantly lower levels of 24-hour systolic BP, night diastolic BP and minimal night systolic BP. Re-adjustment of antihypertensive treatment on the 10-th postoperative day was required to 2 (10%) patients with hypotension episodes and to 1 (4.5%) patient with BP elevation. Correction of antihypertensive therapy was required to all patients in LSN group on the day 2, and to 32 (60.4%) patients on the 10-th day after the operation. Reduction in the incidence of complications (from 1.2% in 2009 to 0.3% in 2011, p<0.001) was observed during the application of cardiovascular non-invasive complex assessment and preoperative preparation in hypertensive patients.Conclusion. The elaborated management algorithm for patients with concomitant hypertension is recommended to reduce the cardiovascular complications in the early postoperative period.